A molecular perspective on the invasibility of the southern ocean benthos: The impact of hypoxia and temperature on gene expression in South American and Antarctic Aequiyoldia bivalves - Martínez, Mariano; González-Aravena, Marcelo; Held, Christoph; Abele, Doris (Frontiers in Physiology, 2023)
When an organism makes a long-distance transition to a new habitat, the associated environmental change is often marked and requires physiological plasticity of larvae, juveniles, or other migrant stages. Exposing shallow-water marine bivalves (Aequiyoldia cf. eightsii) from southern South America (SSA) and the West Antarctic Peninsula (WAP) to changes in temperature and oxygen availability, we investigated changes in gene expression in a simulated colonization experiment of the shores of a new continent after crossing of the Drake Passage, and in a warming scenario in the WAP. Bivalves from SSA were cooled from 7 °C (in situ) to 4 °C and 2 °C (future warmed WAP conditions), WAP bivalves were warmed from 1.5 °C (current summer in situ) to 4 °C (warmed WAP), gene expression patterns in response to thermal stress by itself and in combination with hypoxia were measured after 10 days. Our results confirm that molecular plasticity may play a vital role for local adaptation. Hypoxia had a greater effect on the transcriptome than temperature alone. The effect was further amplified when hypoxia and temperature acted as combined stressors. The WAP bivalves showed a remarkable ability to cope with short-term exposure to hypoxia by switching to a metabolic rate depression strategy and activating the alternative oxidation pathway, whilst the SSA population showed no comparable response. In SSA, the high prevalence of apoptosis-related differentially expressed genes especially under combined higher temperatures and hypoxia indicated that the SSA Aequiyoldia are operating near their physiological limits already. While the effect of temperature per se may not represent the single most effective barrier to Antarctic colonization by South American bivalves, the current distribution patterns as well as their resilience to future conditions, can be better understood by looking at the synergistic effects of temperature in conjunction with short-term exposure to hypoxia.